x*(x-a^2)*(x+b-a^2)*(x+a^2)*(x+b+a^2)+y^2-z^2 = 0 for (a = 0, b = 0.36)

(x^2+y^2+z^2-(0.5+2*a)^2)^2-(3.0*((0.5+2*a)^2)-1.0)/(3.0-((0.5+2*a)^2))*(1-z-sqrt(2)*x)*(1-z+sqrt(2)*x)*(1+z+sqrt(2)*y)*(1+z-sqrt(2)*y) = 0 for (a = 0.43)

x^3+y^3+z^3+1-0.5*a*(x+y+z+1)^3 = 0 for (a = 1)

x*y*z = 0

(x^2+9/4*y^2+z^2-1)^3-x^2*z^3-9/80*y^2*z^3 = 0

x^2/(a+0.05)^2+y^2/(b+0.05)^2-z^2-1 = 0 for (a = 1, b = 1)

x^3+y^3+z^3+1-0.5*a*(x+y+z+1)^3 = 0 for (a = 1)

All the above graphs were generated using Surfer software. It ire real fun to play with it and vizualize the equations.

Advertisements

## Comments